2022
DOI: 10.3389/fimmu.2022.861583
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Mediate Immune Responses to Tissue-Associated Self-Antigens: Role in Solid Organ Transplantations

Abstract: Transplantation is a treatment option for patients diagnosed with end-stage organ diseases; however, long-term graft survival is affected by rejection of the transplanted organ by immune and nonimmune responses. Several studies have demonstrated that both acute and chronic rejection can occur after transplantation of kidney, heart, and lungs. A strong correlation has been reported between de novo synthesis of donor-specific antibodies (HLA-DSAs) and development of both acute and chronic rejection; however, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 179 publications
(200 reference statements)
0
6
0
Order By: Relevance
“…Our group has recently identified exosomes in circulation that carry donor HLAs and lung-associated SAgs (Col-V and Kα1T) after LTx, 11,46 and furthermore, that levels of exosomes with SAgs increased in circulation before clinical evidence of rejection. 10 Several studies have demonstrated that exosomes play a crucial role in carrying and presenting functional major histocompatibility peptide complexes to modulate antigen-specific T-cell responses 11,46,75,76 and that exosome-mediated allorecognition can involve both innate and adaptive immunity. Finally, antigen-carrying exosomes found in circulation after transplantation may also be useful as an early biomarker of rejection.…”
Section: Evs and Antigen Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has recently identified exosomes in circulation that carry donor HLAs and lung-associated SAgs (Col-V and Kα1T) after LTx, 11,46 and furthermore, that levels of exosomes with SAgs increased in circulation before clinical evidence of rejection. 10 Several studies have demonstrated that exosomes play a crucial role in carrying and presenting functional major histocompatibility peptide complexes to modulate antigen-specific T-cell responses 11,46,75,76 and that exosome-mediated allorecognition can involve both innate and adaptive immunity. Finally, antigen-carrying exosomes found in circulation after transplantation may also be useful as an early biomarker of rejection.…”
Section: Evs and Antigen Presentationmentioning
confidence: 99%
“…EVs possess both physiological and pathological roles, and emerging evidence suggests that EVs can induce rejection of solid organ transplants by a semidirect pathway and can also participate in the induction of tolerance. 76,131,132 An earlier study found that EVs with HLA G and Fas ligand were involved in maternal immune tolerance. Recent data demonstrate that placenta-derived EVs significantly modulate immune responses leading to maternal immune tolerance during pregnancy.…”
Section: Evs and Allograft Tolerancementioning
confidence: 99%
“…The origin of EVs can be ectosomal or endosomal. They are divided on the basis of size: (a) microvesicles (100-1,000 nm); (b) apoptotic bodies (1,000-5,000 nm); (c) exosomes/small EVs <200 nm (71,72) (Figure 1). There are multiple terms associated with the nomenclature of EVs and exosomes as per Minimal Information for Studies of Extracellular Vesicles (MISEV) guidelines.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“… Diagrammatic reprentation of extracellular vesicle carrying CD9, CD63, CD81, TSG101, ALIX, tissue-specific markers (collagen V and K alpha1 tubulin in lung transplant; cardiac myosin and vimentin in cardiac transplant; fibronectin, collagen IV and perlecan in kidney transplant) ( 73 ). Images created using BioRENDER.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…EVs play a role in cell-to-cell communication in various physiological processes as they carry, e.g., proteins, carbohydrates, lipids, messenger RNAs (mRNAs), and microRNAs that can interact with target cells [3]. In the regulation of inflammation, they have now been recognized as potential biomarkers and immune mediators in organ transplantation [4].…”
Section: Introductionmentioning
confidence: 99%